(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify cognitive achievement and its reflection on future anxiety before volleyball competitions among preparatory school students. The research problem appears through the anxiety of some students before competitions to present their best performance and their fear of not being able to achieve their goals, dreams and ambitions, whether in achieving good results by winning matches or other future goals and ambitions. Their feeling of anxiety has become a clearly noticeable phenomenon, as the researcher noticed that preparatory school students go through a series of events that put pressure on them and are imposed by a series of huge changes and their complex data in various areas of their lives. These successive events contribute to the spread of new behavioral patterns among students that impose themselves on them as a natural reaction to these rapid changes that increase the pressures that confront the student who finds himself face to face with new situations and matters that he must deal with and confront or surrender to them. The researcher used the descriptive approach for its suitability to the nature of the problem and the objectives of the research. The research community was represented by the students of the secondary stage of Educational Rusafa Directorate II, Educational Directorate of Eastern Baghdad, participating in the school volleyball championship and distributed over (8) secondary schools, namely (Samarra, Sayyid al-Shuhada, Ibn al-Baytar, Bashar ibn Burd, Bilad al-Nahrain, Marouf al-Rusafi, Ibn Khaldun, Ahmed al-Waili, al-Sanabel), with a total of (100) students. The research sample was represented by the students of Samarra Preparatory School in volleyball, with a total of (22) students, representing (22%) of the original community and (4) students were excluded from them, representing the exploratory experiment. Thus, the final group of the research sample was (18) students. Two questionnaires were used on the researched sample, and the data were processed statistically using the statistical program (SPSS). The researcher concluded that there is an inverse significant relationship between cognitive achievement and future anxiety. The researcher recommends taking into account cognitive achievement when developing educational curricula and annual plans for academic stages in order to enable students to confront the changes they encounter during their academic life and overcome them through the cognitive aspect they possess.